Effects of various mastitis treatments on the reproductive performance of cows - Sebastian Smulski; Marek Gehrke; Kacper Libera; Adam Cieslak; Haihao Huang; Amlan Kumar Patra; Malgorzata Szumacher-Strabel (BMC Veterinary Research, 2020)
Abstract Background The purpose of the study described here was to evaluate the effects of different supportive treatments - such as antioxidants, immunomodulators, and nonsteroidal anti-inflammatory drugs (NSAIDs) - in mastitic cows treated with intramammary antibiotics on the efficacy of mastitis therapy and fertility indices. Fertility indices, including time to first insemination, conception rate, time between calving and conception (open days), and number of services per conception (insemination index), were evaluated for 300 dairy cows. Sixty cows without apparent clinical signs of mastitis were assigned 100 days after calving to a Control group. Another 240 cows with clinical mastitis were systematically divided into four experimental groups (I–IV) of 60 cows each. All mastitic cows were treated with approved intramammary antibiotics in recommended doses. Cows in Group I were treated with intramammary antibiotics only. Cows in Groups II, III, and IV, received intramammary antibiotic therapy and a single injection with antioxidants, an immunomodulator (lysozyme dimer), or an NSAID (flunixin meglumine), respectively. Results The lowest treatment efficacy of mastitic quarters and cows was noted in Group I (51.6 and 53.3%; p > 0.05). The best recovery rate was noted in Group II (63.3 and 66.7%; p > 0.05), followed by Group III (58.3 and 60.9%) and Group IV (58.3 and 58.0%; p > 0.05). The above data did not differ statistically (p > 0.05). The animals with mastitis (Groups I–IV) showed prolonged time to first insemination, more open days, higher insemination index, and lower conception rate than the control cows (p <  0.05). The conception rate of healthy cows and of successfully treated cows was insignificantly lower than that of cows required prolonged antibiotic therapy. Supportive treatments improved the mastitis recovery rate compared with intramammary antibiotics only. The efficacy of mastitis treatments affected the reproduction indices: in cows requiring prolonged treatment with antioxidants, a shorter time to first insemination was needed than in other groups (p <  0.05). Fewer days open were observed between the group with antioxidants and the control group (p <  0.05). Conclusions Clinical mastitis negatively affects reproductive indices (days open, pregnancy rate after first AI, NSC) in dairy cows. Different types of supportive medicine, such as antioxidants (vitamin C and E, and β-carotene), lysozyme dimer, or NSAID can be useful in improving fertility in mastitis cows treated with antibiotic only. It has been proven that each supportive treatment improved antibiotics efficiency and the antibiotic combined with the antioxidants was the most effective treatment.